A Little Book of Language - Crystal, David (Sydney : University of NSW Press, 2010)
With a language disappearing every two weeks and neologisms springing up almost daily, an understanding of the origins and currency of language has never seemed more relevant. In this charming volume, a narrative history written explicitly for a young audience, expert linguist David Crystal proves why the story of language deserves retelling. From the first words of an infant to the peculiar modern dialect of text messaging, A Little Book of Language ranges widely, revealing language's myriad intricacies and quirks.
TextingLanguage at play; Untitled; Language for feelings; Political correctness; Language in literature; Developing a style; The complexity of language; Linguistics; Applied linguistics; Your language world; Index
Description based upon print version of record.
Keywords: Language and languages